1955
DOI: 10.1152/ajplegacy.1955.183.2.302
|View full text |Cite
|
Sign up to set email alerts
|

Over-All Glucose Utilization in Steroid Diabetic Guinea Pigs

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1957
1957
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Continued, chronic adrenal steroid secretion or administration has previously been shown to produce ß cell hyperplasia: (a) in a patient with adrenocortical adenoma (Lukens, Flippin and Thigpan. 1937) (Haist 1959), guinea pigs (Hausberger and Hausberger 1955) and rabbits (Volk and Lazams 1963). An increase of insulin in blood was found by in Chinese hamsters following glucosteroid treatment of pharmacological doses.…”
Section: Discussionmentioning
confidence: 99%
“…Continued, chronic adrenal steroid secretion or administration has previously been shown to produce ß cell hyperplasia: (a) in a patient with adrenocortical adenoma (Lukens, Flippin and Thigpan. 1937) (Haist 1959), guinea pigs (Hausberger and Hausberger 1955) and rabbits (Volk and Lazams 1963). An increase of insulin in blood was found by in Chinese hamsters following glucosteroid treatment of pharmacological doses.…”
Section: Discussionmentioning
confidence: 99%
“…As neither GP received medications including glucocorticoids, steroid-induced diabetes mellitus (as previously described in experimental settings) could be ruled out [23,24]. Simultaneously, a spontaneous hyperadrenocorticism in two young GPs was considered unlikely and no other signs such as alopecia, potbelly, or muscle wasting were observed [29].…”
Section: Discussionmentioning
confidence: 98%
“…In addition to type I and type II DM, other types of DM like gestagen-and steroidinduced DM have been reported in GPs. Therefore, individual treatment approaches are necessary to optimize treatment success in this species [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Rapid inhibition of glucose utilization in vitro by various non-hepatic organs of mouse and rat has also been clearly demonstrated (Morgan, Henderson, Regen & Park, 1959;Overell, Condon & Petrow, 1960 Leboeuf, Renold & Cahill, 1962;Munck, 1962). Similarly, it has been shown that, in the longer term (24 h or more), corticosteroid administration causes increased hepatic gluconeogenesis with increased hepatic release of new glucose in rats, guinea-pigs, dogs, man and sheep (Long, Katzin & Fry, 1940;Wick, Drury & McKay, 1951 ;Welt, Stetten, Ingle & Morley, 1952;Hausberger & Hausberger, 1955;Altszuler, Steele, Wall & De Bodo, 1957;Fabrykant, Jackson & Ashe, 1957;Ford & Winchester, 1974).…”
Section: Metabolic Clearance Ofglucosementioning
confidence: 93%